BIOLOGIC REACTIONS AT ACL GRAFT INSERTION SITES MEASURED BY 99MTC-HDP-SPECT/CT TRACER UPTAKE. Issue 10 (10th June 2013) - Arnold, Markus; Mathis, Dominic; Rasch, Helmut; Testa, Enrique Adrian; Friederich, Niklaus; Hirschmann, Michael Tobias
Abstract : Introduction: Not much is known about biologic reactions at ACL graft insertion sites. SPECT/CT is a hybrid imaging modality, which combines a 3D single photon emission computed tomography and a conventional computerized tomography. It allows accurate anatomical localization of metabolic tracer activity and allows therefore the correlation of surgical factors such as tunnel position and orientation with mechanical alignment, clinical outcome and biological factors. The purpose of this study is to investigate the correlation between SPECT/CT tracer uptake (intensity and distribution) and the stability and laxity of the knee joint and also the position and orientation of the tibial and femoral tunnels in patients after ACL reconstruction. Methods: A consecutive series of patients (n=66), which were complaining about pain and/or instability after ACL reconstruction were prospectively evaluated using clinical examination and 99mTc-HDP-SPECT/CT. Clinical laxity testing was performed including Lachman's test (0–2 mm, 3–5 mm, 6–10 mm, >10 mm), anterior drawer test (0–2 mm, 3–5 mm, 6–10 mm, >10 mm), pivot shift test (positive/negative) and patient-based subjective instability (yes/no). For analysis of SPECT/CT tracer uptake a previously validated SPECT/CT localization scheme consisting of 17 tibial, 9 femoral and 4 patellar regions on standardized axial, coronal, and sagittal slices, was used. The tracer activity on SPECT/CT was localized and recorded using a 3D volumetric and quantitative analysis software. Mean, standard deviation, minimum and maximum of grading for each area of the localization scheme were recorded. The position and orientation of the tibial and femoral tunnel was assessed using a previously published method on 3D-CT. Results: Characteristics of instability, pivot shift as well as clinical laxity testing with 99mTc-HDP-SPECT/CT tracer uptake intensity and distribution showed no significant correlation. The tracer uptake correlated significantly with the position and orientation of the ACL graft. A more horizontal femoral graft position showed significant more increased tracer uptake within the superior and posterior femoral regions. A more posterior placed femoral insertion site showed significant more tracer uptake within the femoral and tibial tunnel regions. A more vertical or a less medial tibial tunnel orientation showed significant increased uptake within the tibial and femoral tunnel regions. A more anterior tibial tunnel position showed significant more tracer uptake in the femoral and tibial tunnel regions as well as the entire tibiofemoral joint. Conclusions: SPECT/CT tracer uptake intensity and distribution showed a significant correlation with the femoral and tibial tunnel position and orientation in patients with symptomatic knees after ACL reconstruction. No correlation was found with stability or clinical laxity. SPECT/CT tracer uptake distribution has the potential to give us important information on joint homeostasis and remodeling after ACL reconstruction. It might help to improve our surgical ACL reconstruction technique by directing us to find the optimal tunnel position based on the results of biological activity with the achievement of joint homeostasis being our goal.